Recent Publications (Quarterly Journal of Economics, 1936)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 50, Issue 2, February 1936, Pages 372–376, https://doi.org/10.1093/qje/50.2.372 Published: 01 February 1936